The Light Cupula: An Emerging New Concept for Positional Vertigo - Kim, Min-Beom; Hong, Seok Min; Choi, Hyerang; Choi, Seongjun; Pham, Ngoc Chien; Shin, Jung Eun; Kim, Chang-Hee (Journal of audiology & otology, 2018)
Benign paroxysmal positional vertigo (BPPV) is the most common type of positional vertigo. A canalolithiasis-type of BPPV involving the lateral semicircular canal (LSCC) shows a characteristic direction-changing positional nystagmus (DCPN) which beats towards the lower ear (geotropic) on turning the head to either side in a supine position. Because geotropic DCPN in LSCC canalolithiasis is transient with a latency of a few seconds, the diagnosis can be challenging if geotropic DCPN is persistent without latency. The concept of "light cupula" has been introduced to explain persistent geotropic DCPN, although the mechanism behind it requires further elucidation. In this review, we describe the characteristics of the nystagmic pattern in light cupula and discuss the current evidence for possible mechanisms explaining the phenomenon.